Efektivitas Kepemimpinan Kepala Sekolah dalam Manajemen Konflik - Dessy Fitria (Journal Innovation In Education, 2025)
It is very important for the principal to influence and direct the school staff. This is done to ensure that the school's goals can be achieved through the cooperation of all components. Teachers' performance in carrying out the task of educating students is determined by their motivation to work. Therefore, teacher performance can be affected by good principal leadership. The purpose of this study is to find out how effective the principal's leadership is in handling conflicts at UPT SMP Negeri 1 Gresik, Jawa Timur. The paradigm of this research is qualitative. However, the approach used is a case study. Interviews, observations, and documentation studies are all methods of data collection. The results of the study show that democratic leadership also known as a competent principal is able to reduce conflicts in schools.